PERAN AGAMA SEBAGAI SARANA KOMUNIKASI DALAM MEMBANGUN SOLIDARITAS SOSIAL: PERSPEKTIF EMILE DURKHEIM - Mokoginta, Ario Gardamong (Program Studi Manajemen Dakwah Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2025)
Religion has an important role in the life of humans. Not only as a belief system, but also as the medium to build solidarity inside the society. In various cultures and societies, religion plays the role of a uniting factor that connects individuals with its group, giving moral guidance, and strengthens their social bond. In Durkheim’s perspective, the existing social solidarity built through religion does not only create similarities, but also manage the differences between individuals, in order to maintain balance in the social structure. This research aims to explore how religion plays a role as the communication medium in building social solidarity inside Indonesia’s society, through Emile Durkheim’s perspective. This research is a library research with the approach being qualitative. The result shows that religion does indeed play a very important role in building social solidarity in the society. From Emile Durkheim’s perspective, religion is not only a spiritual belief system but also function as a social communication medium able to create harmony between individuals and communities. In a traditional society, mechanic solidarity is formed by common religious beliefs, norms, and values shared together. Religion in this scope becomes the main binder that strengthens social relations, maintaining stability in the community. On the other hand, in a modern and more complex society, organic solidarity develops through interdependency under the influence of religion as the moral guidance and liasion between groups. Through symbols, rituals, and moral values, religion creates collective awareness that serves as the foundation of social solidarity.